Role of Education concerning the Gross Domestic Product, Human Development Index and Poverty Rate in East Java - Sukidin Sukidin; Wiwin Hartanto; Retna N Sedyati; Shofiyah Shofiyah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research was purposed to know the role of education and to analyze the relationships of Gross Regional Domestic Product (GRDP) and Human Development Index (HDI) on poverty rate in East Java Province. The used research method was quantitative research. This research used secondary data obtained from the Central Bureau of Statistics of East Java. The data were analyzed by using panel data regression analysis with Fixed Effect Model (FEM) estimation and the aid of EViews 9.0 application program. The research result showed that PDRB and HDI variables affected simultaneously poverty rate in East Java Province from 2010 to 2016 that was 97.8506%. GRDP variable affected partially poverty rate that was -0.251899, and HDI variable affected partially as well poverty rate that was -1.868236. To support the increment of human development index (HDI), it is necessary to enhance the role of education. It is generally accepted that a person's HDI income level will improve as their degree of education increases. This is achievable due to the fact that educated people tend to be more productive overall.